CONTEMPORARY APPROACHES TO PRIMARY EDUCATION METHODOLOGY - Sheranova Guzal Ravshanovna (Modern American Journals, 2025)
This article explores the evolving methodology of primary education, with a focus on pedagogical strategies, learner engagement, and curriculum development. Drawing from recent academic literature and empirical studies, it examines the key principles that guide effective teaching practices in early childhood education. The paper reflects on learner-centered approaches, the integration of digital tools, and the role of formative assessment in shaping primary learners' experiences. The analysis is grounded in current educational research and aims to provide insights for educators, policymakers, and scholars interested in refining teaching practices in the early years of schooling.
Keywords: Primary education, pedagogy, teaching methodology, learner-centered, formative assessment, curriculum, digital learning.